Anthropomorphic Figurines and Fragments from Neolithic Crete and Thessaly: Analysis of their context, age, sex and gender - Ramirez Valiente, Paz (2022)
This thesis examines the subjects of context, age, sex and gender in the Neolithic Aegean, focusing on the regions of Crete and Thessaly through an analysis of anthropomorphic figurines. Studying the figurines' archaeological contexts aims to shed light on the uses and practices involving Neolithic figurines through a methodology that recognises structured deposition as part of ritual practices. The main aim of studying age, sex and gender is to understand the meaning of figurines that do not show sex indication (Asexual), as well as those that show sex ambiguously (Probably Female/Male) or present sexual traits of both sexes (Double-sex). The thesis is organised into eight chapters. Chapter I presents the aims and research questions of the thesis and a short introduction to the sample of figurines analysed and the chronological framework of the Neolithic Aegean. Chapter II delves into the main literature and contributions of previous studies on anthropomorphic figurines and the theoretical approaches previously applied. In Chapter III, I apply a methodology to understand Neolithic ritual practices through the recognition of structured deposition. I further review the available archaeological evidence for the findspot context of figurines and how it may be interpreted. Chapter IV establishes a methodology to recognise age-stages in Neolithic figurines from Crete and Thessaly and then presents the results of possible age differences with evidence from figurines and burials. Chapter V presents the analysis of sex and gender with a methodology developed for figurines from Neolithic Greece. Chapter VI examines colour and decoration on Neolithic figurines and their relationship with sex, gender and age. I also explore the possible meanings of figurines' decoration as representing clothing or textile patterns, scarification or tattooing, body painting, jewellery and headdress. Chapter VII outlines the main results and findings of the thesis regarding the analysis of context, age, sex and gender. I further discuss the results and offer a series of interpretations of the uses and practices involving figurines such as fragmentation, foundation deposits, ritualised food consumption, rites of abandonment or closure, and rites of passage. In the final section, I delve deeper into the possible interpretations of Asexual and Double-sex figurines. Chapter VIII summarises the main contributions of my research to the knowledge of Neolithic social organisation in diverse regions of Greece. I highlight the need to apply new methodologies to the study of prehistoric ritual that are not completely subjective and the importance of applying new approaches that understand gender from an intersectional perspective considering other axes of difference such as age.